Investigation of the fuel consumption of a ship considering the dynamic coupling effect among resistance, propeller torque and engine power under the control of a governor - Beh, Gerald Kah Hooi (Nanyang Technological University, 2023)
Over the past century, the maritime industry has seen an uptick in demand for shipping and other related services due to increasing globalisation. Year after year, ships are getting bigger, ports are getting increasingly congested, and more and more ships continue to be built to service the thriving maritime sector. However, from an environmental standpoint, shipping continues to be a large contributor to greenhouse gas emissions as large amounts of fuel are consumed on every passage. This problem has become so pervasive that the International Maritime Organisation has imposed new regulations to reach decarbonisation by the year 2035. Methods to achieve this include improving ship design to reduce ship resistance, or simply reducing speed. Given the extensive costs involved to upgrade an existing ship in the fleet, it is likely that most ship owners will choose to reduce their ships’ speed.